ANALISIS FINANSIAL SISTEM ALOKASI AIR DI DESA SIDOMULYO - Rizka Khalifatul Jannah (JURNAL AGROTEKNOLOGI, 2012)
The purposes of this research are to know the value of investments, investment feasibility, the value of PBP, BEP, and to provide the alternative of potential water use in the future. This research was conducted by using field observations of the location and pipeline layout to distribute the water reservoir in residential area using GPS. The methodsof data collection are question and answer method, study of  literature, and data processing (to determine the value of investment and potential use of water for agriculture, livestock, water treatment) and calculate of economic feasibility analysis using mathematical formulas. The study shows that the use of investment amounting to Rp.276.209.295, the contributions of citizens and the three agencies was declared unfit with a payback more than 20 years. If using the potential use of water is obtained 67861847 NPV more than 0 (feasible), 19,7 % IRR ≥ MARR of 14% (feasible), and BCR value of 5,0 more than 1 (feasible). Investment return in 3,6 years, the BEP occur if residents use as much as 572.418.490 liter of water, coffee mill 101.429.658 liter, 48.189 liters of water treatment, agriculture and animal husbandry of 1.908.061.967 liter. Annual benefit of water treatment. Rp.45.000.000 and livestock farming Rp.11.625.840/year.Keywords: water allocation, investment feasibility, potential water use